2019
DOI: 10.1017/jfm.2019.292
|View full text |Cite
|
Sign up to set email alerts
|

Pseudophase change effects in turbulent channel flow under transcritical temperature conditions

Abstract: We have performed direct numerical simulations (DNS) of compressible turbulent channel flow at supercritical pressure with top and bottom isothermal walls kept respectively at a supercritical (T top > T pb ) and subcritical temperature (T bot < T pb ), where T pb is the pseudoboiling temperature. The DNS are conducted using a high-order discretization of the fully compressible Navier-Stokes equations in conservative form closed with the Peng-Robinsion (PR) state equation. Bulk density is adjusted to obtain a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Toki, Teramoto & Okamoto (2020) also simulated a planar turbulent channel flow of supercritical nitrogen and introduced a new transformation equation for the temperature profile in the logarithmic region. Transcritical channel flow of R-134a was simulated by Kim, Hickey & Scalo (2019) and it was reported that even the recent improvements to the scaling laws cannot accurately capture the velocity distribution in that transcritical flow.…”
Section: Introductionmentioning
confidence: 99%
“…Toki, Teramoto & Okamoto (2020) also simulated a planar turbulent channel flow of supercritical nitrogen and introduced a new transformation equation for the temperature profile in the logarithmic region. Transcritical channel flow of R-134a was simulated by Kim, Hickey & Scalo (2019) and it was reported that even the recent improvements to the scaling laws cannot accurately capture the velocity distribution in that transcritical flow.…”
Section: Introductionmentioning
confidence: 99%
“…A fourthorder Runge-Kutta scheme is used for the time integration. The solver has been rigorously validated in the case of shock-turbulence interactions 27 and wall-bounded flows, 29 and the accuracy of the numerical schemes is well established. 30…”
Section: B Numerical Methodsmentioning
confidence: 99%
“…At turbulent conditions in the transcritical regime, the presence of both liquid-like and gas-like thermodynamic property dependencies yields two spatial regions in the fluid domain, each with distinctive behaviour as influenced by the thermodynamics. Compared with classical constant-property trends, observations of turbulence in the gas-like region have shown -among other features -increased overall streamwise and spanwise anisotropy, enlarged spanwise spacing of large-scale near-wall structures (Patel et al 2015), and intensified relative turbulent fluctuation levels of thermodynamic transport properties (Kim, Hickey & Scalo 2019). Reverse trends have been observed in the liquid-like regime.…”
Section: Introductionmentioning
confidence: 93%
“…Additionally, in realistic transcritical flows, these coupled effects of modulated turbulence and property variations can be combined with a number of other physical phenomena, including thermoacoustic oscillations and buoyancy, all of which contribute towards further modification of the resultant turbulence dynamics and heat transfer, as discussed in Kim et al (2019) and Nemati et al (2015). The presence of buoyancy effects can cause transcritical fluids to undergo significant reduction in the magnitude of heat transfer.…”
Section: Introductionmentioning
confidence: 99%